Prolyl Hydroxylase Domain-2 Inhibition Improves Skeletal Muscle Regeneration in a Male Murine Model of Obesity - Sinha, Indranil; Sakthivel, Dharaniya; Olenchock, Benjamin A.; Kruse, Carla R.; Williams, Jeremy; Varon, David E.; Smith, Jessica D.; Madenci, Arin L.; Nuutila, Kristo; Wagers, Amy J. (Frontiers in Endocrinology, 2017)
Obesity leads to a loss of muscle mass and impaired muscle regeneration. In obese individuals, pathologically elevated levels of prolyl hydroxylase-domain enzyme 2 (PHD2) limit skeletal muscle hypoxia-inducible factor-1 alpha (HIF-1α) and vascular endothelial growth factor (VEGF) expression. Loss of local VEGF may further impair skeletal muscle regeneration. We hypothesized that PHD2 inhibition would restore vigorous muscle regeneration in a murine model of obesity. Adult (22-week-old) male mice were fed either a high-fat diet (HFD), with 60% of calories derived from fat, or a regular diet (RD), with 10% of calories derived from fat, for 16 weeks. HFD mice gained weight and exhibited elevated fasting serum glucose levels compared to mice fed an RD. On day 5 following cryoinjury to the tibialis anterior muscle, newly regenerated muscle fiber cross-sectional areas were significantly smaller in mice fed an HFD as compared to RD, indicating an impaired regenerative response. Cryoinjured gastrocnemius muscles of HFD mice also showed elevated PHD2 levels (2-fold higher) and reduced VEGF levels (2-fold lower) as compared to RD. Dimethyloxalylglycine (DMOG), a cell permeable competitive inhibitor of PHD2, restored VEGF levels and significantly improved regenerating myofiber size in cryoinjured mice fed an HFD. We conclude that pathologically increased PHD2 in the obese state drives impairments in muscle regeneration, in part by blunting VEGF production. Inhibition of PHD2 over activity in the obese state normalizes VEGF levels and restores muscle regenerative potential.